Quickly evolving near‐infrared photoimmunotherapy provides multifaceted approach to modern cancer treatment. Issue 3 (27th August 2021) - Monaco, Hailey; Yokomizo, Shinya; Choi, Hak Soo; Kashiwagi, Satoshi
Abstract: Among modalities of cancer immunotherapy, near‐infrared photoimmunotherapy (NIR‐PIT) has reached significant preclinical and clinical stages and quickly evolved over the last 5 years. NIR‐PIT uses deep‐penetrable NIR light to induce physicochemical changes in the antibody–photosensitizer conjugate (APC), leading to resultant necrosis and immunogenic cell death (ICD) of the cancer cells. Alternatively, other types of photomedicine use photosensitizers to convert absorbed light energy either into reactive oxygen species for photodynamic therapy (PDT) or into heat for photothermal therapy (PTT). ICD is a unique and relevant outcome of NIR‐PIT because it induces long‐lasting antitumor host immunity, which overcomes the immunosuppressive network of cancer. Due to its high specificity and durable antitumor effects, NIR‐PIT is now considered a promising cancer therapy, and optimized NIR‐PIT is readily expanding its applicability to many different types of cancer. Along with the traditional method of NIR‐PIT, new avenues in its realm of treatment are currently being explored, such as the targeting of other immunosuppressive elements, delivery of NIR light through a catheter, real‐time imaging for tumor detection, and the use of tumor‐seeking small molecules for improved efficacy and safety. In addition, its effect on hyperpermeability has opened a door for a wide array of combination therapies with other modalities. This review summarizes the recent findings in clinical and preclinical studies of NIR‐induced photomedicine and its future significance in the field of cancer research. Abstract : Near‐infrared photoimmunotherapy (NIR‐PIT), which demonstrated recent preclinical and clinical success, is an expansion on the field of photomedicine. NIR‐PIT shows remarkable therapeutic effects inducing long‐lasting antitumor host immunity via inducing immunogenic cell death and would soon establish a new class of cancer therapy. Compared to other photomedicines inducing weak immune responses, NIR‐PIT evokes robust anticancer immunity via release of damage‐associated molecular patterns.